2002
DOI: 10.2527/2002.8071947x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascophyllum nodosum extract on growth performance and immune function of young pigs challenged with Salmonella typhimurium1

Abstract: Ninety-five pigs (initially 7.1 kg and 24 d of age) were used in a 28-d experiment to determine the effects of Ascophyllum nodosum seaweed extract (ANOD) on young pig growth performance and immune function in response to enteric disease challenge with Salmonella typhimurium (ST). Experimental treatments were arranged in a 2 x 4 factorial with main effects of disease challenge (control vs ST-challenge) and dietary addition of ANOD (0, 0.5, 1.0, and 2.0% of diet). Pigs were fed ANOD diets for 14 d and then chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 6 publications
5
63
2
3
Order By: Relevance
“…This is similar to the results demonstrated by Turner et al (2002) and Gardiner et al (2008), when this type of product is administered close to the weaning age, providing a longer period of time for the digestive system to improve the animals' physiological efficiency in the following production periods.…”
Section: Discussionsupporting
confidence: 77%
“…This is similar to the results demonstrated by Turner et al (2002) and Gardiner et al (2008), when this type of product is administered close to the weaning age, providing a longer period of time for the digestive system to improve the animals' physiological efficiency in the following production periods.…”
Section: Discussionsupporting
confidence: 77%
“…However, it can be attributed to the increased feed intake of pigs supplemented with the laminarin and fucoidan extract. Increased feed intake was also reported in previous pig-feeding studies (Allen et al, 2001;Turner et al, 2002) to seaweed extract supplementation. Pluske et al (1996) demonstrated that villus height and crypt height could be maintained if piglets do not suffer the nutritional stress associated with interrupted feed intake immediately post weaning.…”
Section: Discussionmentioning
confidence: 48%
“…The use of seaweed extracts in pig diets has given variable responses (Allen et al, 2001;Turner et al, 2002;Gardiner et al, 2008). Gardiner et al (2008) reported linear decreases in daily gain as the level of an Ascophyllum nodosum extract increased in healthy grower-finisher pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, a dose of 10 mg/ml of A. nodosum (greatly exceeding the highest level of feed incorporation level of 2%) was able to activate porcine alveolar macrophages to secrete prostaglandin E2. However, this dose did not alter the secretion of IL-10 by splenocytes (Turner et al, 2002a). Taken together, the in vitro and in vivo data suggest that A. nodosum extract probably has only little direct effect on gut immune system in pig.…”
Section: In-feed Modulators Of Piglet Immunitymentioning
confidence: 67%
“…To date, we are only aware of one study that presents data on influence of a seaweed extract on the immune parameters in pig production. This extract was derived from Ascophyllum nodosum, and different levels of incorporation ranging from 0% to 2% were tested in piglets orally challenged with 6 3 10 9 CFU (colony forming units) of Salmonella enterica serovar Typhimurium (Turner et al, 2002a). Increasing levels of A. nodosum tended to linearly enhance the feed intake, but decreased the feed efficiency during the 4 weeks following the weaning of piglets.…”
Section: In-feed Modulators Of Piglet Immunitymentioning
confidence: 99%